EXPLORING STUDENTS’ INTEREST IN BECOMING A TEACHER THROUGH “KAMPUS MENGAJAR” PROGRAM - Nurul Hasanah Fajaria; Indri Nurhasanah (Akademika : Jurnal Teknologi Pendidikan, 2022)
Kampus Mengajar is one of Merdeka Belajar Kampus Merdeka (MBKM) or Independent Learning – Independent Campus program presented by the Ministry of Educational and Culture. This program gives a great chance for university students around Indonesia to participate and impact to the target school. The study was intended to explore the students’ perception of 'Kampus Mengajar' Program on student's interest in becoming a teacher. This research used qualitative design. In data retrieval, researchers are interviewing three students at faculty of teaching and educational sciences of UIA who joined Kampus Mengajar Program batch 3. Based on the results of in-depth interviews, it can be said that the experience of joint Kampus Mengajar Program has influenced college students to become teachers in the future.